STRATEGI PEMERINTAH DALAM PELESTARIAN HUTAN MANGROVE DI DESA SUNGAI DAUN KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR TAHUN 2019 - Suharni "; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Environmental Service of Rokan Hilir Regency and UPT KPH Bagansiapiapi are responsible for the conservation of mangrove forests, the problem of this research is the change in the function of mangrove forests into oil palm plantations and the occurrence of very extensive abrasion in Sungai Daun Village, Pasir Limau Kapas District, Rokan Hilir Regency in 2019. This study aims to find out how the government's strategy is in preserving mangrove forests in Sungai Daun Village, Pasir Limau Kapas District, Rokan Hilir Regency, and what are the inhibiting factors for the government in preserving mangrove forests in Pasir Limau Kapas District, Rokan Hilir Regency in 2019. The research approach used used is a qualitative approach and the type of descriptive research. The location of this research was carried out in Sugai Daun Village, at the Sungai Daun Head Office, the Rokan Hilir Regency Environmental Service Office, the UPT KPH Bagansiapiapi Office, Rokan Hilir Regency, data collection techniques were carried out by interview and documentation.               The results of this study are that first the government's strategy in preserving mangrove forests that has not been maximized can be seen from the coordination between the village government and local governments that have not developed good communication. The change in the function of mangrove forests into oil palm plantations by village communities on the grounds that they do not know the mangrove forest conservation policy is evidence of the failure of communication between local stakeholders and the Rokan Hilir Regency Environmental Service and the authorized UPT KPH Bagansiapiapi. Second, the factors that hinder the government in preserving mangrove forests are the lack of human resources and government coordination. Keywords: Government Strategy, Mangrove Forest Conservation